Distribution of Root-Associated Bacterial Communities Along a Salt-Marsh Primary Succession - Wang, Miao; Yang, Pu; Falcão Salles, Joana (Frontiers in Plant Science, 2016)
Proper quantification of the relative influence of soil and plant host on the root-associated microbiome can only be achieved by studying its distribution along an environmental gradient. Here we used an undisturbed salt marsh chronosequence to study the bacterial communities associated with the soil, rhizosphere and the root endopshere of Limonium vulgare using 454-pyrosequencing. We hypothesize that the selective force exerted by plants rather than soil would regulate the dynamics of the root-associated bacterial assembly along the chronosequence. Our results showed that the soil and rhizosphere bacterial communities were phylogenetically more diverse than those in the endosphere. Moreover, the diversity of the rhizosphere microbiome followed the increased complexity of the abiotic and biotic factors during succession while remaining constant in the other microbiomes. Multivariate analyses showed that the rhizosphere and soil-associated communities clustered by successional stages, whereas the endosphere communities were dispersed. Interestingly, the endosphere microbiome showed higher turnover, while the bulk and rhizosphere soil microbiomes became more similar at the end of the succession. Overall, we showed that soil characteristics exerted an overriding influence on the rhizosphere microbiome, although plant effect led to a clear diversity pattern along the succession. Conversely, the endosphere microbiome was unaffected by any of the environmental measurements and very distinct from other communities.